Arsenic levels present in water supply systems of Chorotega and Huetar Northern Regions of Costa Rica, Central America - Herrera-Murillo, Jorge (2019)
Arsenic (As) concentrations in water samples for human consumption and use were determined in 106 communal supply system operators in the Chorotega and Huetar Norte regions of Costa Rica during 2013-2017. The samples that recorded As concentrations above the national standard were evaluated for the remaining parameters included in level N3 of the Regulation for drinking water of Costa Rica. The determination of arsenic was made using atomic absorption spectrometry with graphite furnace. The main non-compliances were registered in the districts of Bagaces and Cañas, while in the Huetar Norte region they are presented in Agua Zarcas and Los Chiles. In these districts there is a level of non-compliance with the national standard (10 μg / l) that varies from 66.7% in the case of Los Chiles to 50% in Cañas. The systems that present breaches by As did not register significant temporal variations in the 2013-2017 period. When analyzing the parameters of significant correlations recorded between the As and the other species analyzed, valuable information is obtained related to the hydrogeochemical processes that determine the presence of this metalloid.